2023
DOI: 10.1051/0004-6361/202345865
|View full text |Cite
|
Sign up to set email alerts
|

AF Lep b: The lowest-mass planet detected by coupling astrometric and direct imaging data

Abstract: Aims. Using the direct-imaging technique, we searched for low-mass companions around the star AF Lep, which presents a significant proper-motion anomaly (PMa) signal obtained from the comparison of HIPPARCOS and Gaia eDR3 catalogs. Methods. We observed AF Lep in two epochs with VLT/SPHERE using its subsystems IFS and IRDIS in the near-infrared, covering wavelengths ranging from the Y to the K spectral bands (between 0.95 and 2.3 μm). We then reduced the data using the high-contrast imaging techniques angular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…These four stars have all been observed in HCI without detection of close companions; however, the lesson of HIP 25486 = AF Lep b, detected by Mesa et al 24 after previous unsuccessful attempts, tells that the planets may well be there, but they are not detectable in some observations because at that epoch they were projected too close to the star. Indeed, for these targets the probability that the planet is observed when it is not hidden by the coronagraph is rather low (see Table 2).…”
Section: Indications About Planets Not Detected In High Contrast Imagingmentioning
confidence: 88%
See 2 more Smart Citations
“…These four stars have all been observed in HCI without detection of close companions; however, the lesson of HIP 25486 = AF Lep b, detected by Mesa et al 24 after previous unsuccessful attempts, tells that the planets may well be there, but they are not detectable in some observations because at that epoch they were projected too close to the star. Indeed, for these targets the probability that the planet is observed when it is not hidden by the coronagraph is rather low (see Table 2).…”
Section: Indications About Planets Not Detected In High Contrast Imagingmentioning
confidence: 88%
“…Repeated observations are then needed to increase the chance of observing it at the right phase for detection (see e.g. the case of AF Lep b 24,25 ). The implication is that the search of Jupiter-like planets using HCI is likely severely incomplete as HCI surveys typically do not re-observe a star in case of lack of detection of candidate companions.…”
Section: Frequency Of Substellar Companionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample of substellar companions with dynamical masses and age constraints now amounts to ≈20 brown dwarf companions (e.g., Cheetham et al 2018;Brandt et al 2019Brandt et al , 2020Brandt et al , 2021cBonavita et al 2022;Franson et al 2022;Kuzuhara et al 2022;Franson et al 2023a;Li et al 2023) and giant planets (Dupuy et al 2019;Lagrange et al 2019;Nowak et al 2020;Brandt et al 2021a;Hinkley et al 2022;Franson et al 2023b;De Rosa et al 2023;Mesa et al 2023). Most of these benchmark companions orbit old field stars (>1 Gyr); only three planets-β Pic b, β Pic c, and AF Lep b-are young (<200 Myr) and have precise ages based on membership in kinematic associations (Dupuy et al 2019;Nowak et al 2020;Brandt et al 2021a;Franson et al 2023b;De Rosa et al 2023;Mesa et al 2023). 2 Age-dating individual field stars is notoriously challenging, which can limit the precision of model tests for benchmark companions around young field stars (see e.g., HD 984 B; Franson et al 2022) compared to objects in young moving groups.…”
Section: Introductionmentioning
confidence: 99%
“…However, this panorama is expected to be changed in the next few years as the Gaia astrometry mission is going to release about 20,000 giant planet detections with its upcoming data release (DR) 4 (Perryman et al 2014). In fact, with the release of the Gaia DR3 (Gaia Collaboration et al 2023a), we already have dozens of astrometric candidates in the substellar regime (see, e.g., Gaia Collaboration et al 2023b), and a few systems have been identified using Hipparcos and Gaia astrometry, and confirmed by direct imaging (e.g., Currie et al 2023;De Rosa et al 2023;Mesa et al 2023). Astrometry will be especially useful as it can provide us with measurements of the orbital inclinations and true masses of planets (see, e.g., Sozzetti et al 2001;Casertano et al 2008;Perryman et al 2014;Sozzetti et al 2014).…”
Section: Introductionmentioning
confidence: 99%